Homo Seksual Potret Perilaku Seksual Menyimpang Dalam Perspektif Kriminologi, Islam dan Budaya Melayu - Neri Widya Ramailis (UIR PRESS, 2017)
Homosexual is a term used to describe the general tendency of sex with other people of the same genes. Measures of deviant behavior are not in the right or completely wrong size in the general sense, which occur based on the size or absence of norms and values ​​of their sociality. If viewed from the aspect of criminology, deviant behavior becomes something that deviates from the limits determined by the norms and society. Lessons about Malay culture are inseparable from Islamic teachings which are the foundation of customs. Therefore the philosophy of Malay people says